THE THEME OF THE HEART IN THE BYZANTINE TRADITION, RUSSIAN ORTHODOX CULTURE AND RUSSIAN PHILOSOPHY - Makarov, Ivan V. (Russian studies in culture and society, 2023)
The article is devoted to the problem of cardiognosia as the leading one for Russian theological-philosophical and secular religious thought. A special place in Russian (especially in religious) philosophy is occupied by the theme of love and the heart. The main question that we pose in this article is whether the domestic cardiognosy has remained in line with purely Byzantine religious philosophy, or whether our tradition has found an original approach to the study of the heart. This problem is quite relevant due to the fact that modern Russia has often been compared with the Byzantine Empire, such comparative studies have been found for the third decade in various historical, cultural and philosophical studies. The study of the topic of the heart also falls into the piggy bank of spiritual and moral values, to the preservation of which the strategic interests of modern Russian society are addressed. Russian Orthodox culture reveals the theme of the heart in the ascetic tradition of asceticism, and Russian religious philosophy calls the heart the key to understanding the mentality of the Russian person. Modern researchers focus on the integrative function of the heart. Russian Russian Orthodox culture acts as a bridge between Byzantine traditions and Russian philosophy, and modern Russian philosophy considers the heart to be a place of synthesis of science and art culture. The results of the article can be applied in the framework of the creation of the concept of spiritual and moral development and education of the personality of a citizen of Russia.